(untitled) (Studia Prawnicze / The Legal Studies, 2011)
Celem rozważań zawartych w niniejszym artykule jest przedstawienie aktualnych tendencji w orzecznictwie Europejskiego Trybunału Praw Człowieka (dalej jako ETPCz lub Trybunał) na gruncie art. 1 Protokołu nr 1 do Konwencji o Ochronie Praw Człowieka i Podstawowych Wolności (dalej jako EKPCz lub Konwencja) w zakresie skarg skierowanych przeciwko Polsce dotyczących zmian w stosunkach własnościowych dokonanych na gruncie przepisów obowiązujących przed wejściem w życie dla Polski zarówno Konwencji, jak i Protokołu nr 1. Niniejszy artykuł będzie się koncentrował na wskazaniu sytuacji, kiedy skutki zastosowania ustaw nacjonalizacyjnych bądź innych aktów prawnych, które prowadziły do głębokich przekształceń własnościowych, stanowić mogą naruszenie zobowiązań, które Polska zaciągnęła przystępując do Konwencji i Protokołu nr 1. In the article the author considers the current jurisprudence of the ECHR in cases concerning interferences with the property rights that occurred before 10 October 1994, i.e. the moment of entry into force for Poland of Protocol No. 1 to the European Convention on Human Rights. The article concentrates on cases in which the State could be held accountable for the consequences of its acts and omissions that took place before that date. According to the Court’s jurisprudence, Article 1 of Protocol No. 1 cannot be interpreted as imposing any general obligation on the Contracting States to return property which had been transferred to them before they ratified the Convention. Nor does Article 1 of Protocol No. 1 impose any restrictions on the Contracting States’ freedom to determine the scope of property restitution and to choose the conditions under which they agree to restore property rights of the former owners. The hope of recognition of a property right which it has been impossible to exercise effectively cannot be considered a “possession” within the meaning of Article 1 of Protocol No. 1. The Court has also previously considered that legislation in force after the ratification of the Convention and Protocol No. 1 and providing for restoration of property or compensation in lieu of property lost before the Protocol’s entry into force may be regarded as giving rise to a new property right protected by Article 1 of Protocol No. 1 or a legitimate expectation of obtaining the effective enjoyment of a property right. Thus the potential applicants, whose property rights were object of the State’s interference before the entry into force of Protocol No. 1 for Poland, can successfully submit their claims to the Court only in two situations. Firstly, when the applicant can claim being before and after 1994 in the possession of a proprietary interest falling within the ambit of Protocol No. 1. This gave rise to a continuous situation which existed before and after 10 October 1994. Only in limited number of cases concerning situations of interferences the applicants can claim possession of “existing possessions”. Most of the cases concern assets, including claims, in respect of which an applicant can argue that he or she has at least a “legitimate expectation” that they will be realized, i.e. that the applicant will obtain effective enjoyment of a property right. This type of situations encompasses e.g. the so called impaired nationalizations – that means nationalization accompanied by a promise of compensation. In the last years the Court has examined a few cases raising this issue and has undertaken the attempt to define the prerequisites that 93 have to be fulfilled by the impugned compensation provisions in order to be assessed as conferring on the applicant a title to a substantive interest protected by Article 1 of Protocol No. 1. Secondly, the applicants that were deprived of their property before the ratification can refer to the Court in a situation when after the entry into force of Protocol No. 1 the competent authorities declared that the ownership should not have been subject to expropriation. Under the provisions of Polish law such a decision should be regarded as conferring on the applicants a proprietary interest falling within the ambit of possessions within the meaning of Article 1 of Protocol No. 1. According to the Court, the State’s obligation in the circumstances of this case is confined to ensuring effective enforcement of the decision annulling the expropriation, by having in place a legal framework making it possible for the applicants to recover possession of their property and to settle claims arising between them and the private-law entity that was in possession of the property at the time of the impugned decision. Despite the fact that almost 20 years have lapsed from the moment Poland adhered the Convention and Protocol No. 1, there are still cases pending before the Court that concern the legal situations created before the critical date of 10 October 1994. The uncertainty concerning the Court’s ruling affects not only the potential applicant, but also the Government, which can not be sure about the scope of obligations imposed on it according to the Convention and Protocol No 1.